Review of forensic medicine and toxicology including clinical and pathological aspects - Biswas, Gautam (Jaypee Brothers Pvt. Ltd., 2015)
Up-to-date information, substantial amount of material on clinical Forensic Medicine included in a nutshell. Medical Jurisprudence, Identification, Autopsy, Injuries, Sexual Offences, Forensic Psychiatry and Toxicology are dealt with elaborately. Bullet format, easy to understand and concise to read in its entirety. Flow charts, boxes, tables and suitably illustrated with line diagrams. Must know' and 'desirable to know' questions are given in Appendix I & II. Gray colored boxes for recent advances and additional information. Helpful in gaining full understanding of the duties and ethical requ